2016
DOI: 10.1152/physiolgenomics.00105.2015
|View full text |Cite
|
Sign up to set email alerts
|

Athlome Project Consortium: a concerted effort to discover genomic and other “omic” markers of athletic performance

Abstract: Despite numerous attempts to discover genetic variants associated with elite athletic performance, injury predisposition, and elite/world-class athletic status, there has been limited progress to date. Past reliance on candidate gene studies predominantly focusing on genotyping a limited number of single nucleotide polymorphisms or the insertion/deletion variants in small, often heterogeneous cohorts (i.e., made up of athletes of quite different sport specialties) have not generated the kind of results that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 8 publications
1
112
0
2
Order By: Relevance
“…15 A flow diagram displaying information about the subject selection process in this study is shown in Supplemental Figure 1. The present study included 211 Japanese sprint/power track and field athletes (179 men and 32 women) and 649 Japanese nonathletic controls (184 men and 465 women).…”
Section: Methodsmentioning
confidence: 99%
“…15 A flow diagram displaying information about the subject selection process in this study is shown in Supplemental Figure 1. The present study included 211 Japanese sprint/power track and field athletes (179 men and 32 women) and 649 Japanese nonathletic controls (184 men and 465 women).…”
Section: Methodsmentioning
confidence: 99%
“…While exercising, skeletal muscle is challenged to fulfill the mechanical and metabolic demands of contraction, with subsequent increases in its energy expenditure (Hawley, Hargreaves, Joyner, & Zierath, ). Environmental effects such as nutrition, physical activity, and ethnicity all influence performance (Pitsiladis et al., ). Genetic differences also influence skeletal muscle's ability to produce and utilize energy during exercise (Yan, Papadimitriou, Lidor, & Eynon, ) and as such, they might affect training adaptations and athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…e ful llment of great expectations in sports science and medicine from Athlome project, collaborative research project that began in 2015 involving a large number of subjects and based on GWAS studies, will depend largely on bioinformatics interpretation of complex data that will be collected from many analysis during this project. ese results may contribute to a number of new ndings in genetics and genomics of sport and exercise (Pitsiladis, et al, 2016).…”
Section: The Importance Of Bioinformatics In the Interpretation Of Damentioning
confidence: 78%
“…Испуњење великих оче-кивања у спортској науци и медицини од Athlome пројекта, великог колаборативног научног про-јекта који је започео 2015 и у који је укључен ве-лики број испитаника и који је заснован на GWAS студијама, зависиће у највећој мери од биоин-форматичке интерпретације комплексних пода-така који ће се скупити бројним анализама током овог пројекта. Ови резултати би могли допринети бројним новим сазнањима у генетици и геномици спорта и вежбања (Pitsiladis, et al, 2016).…”
Section: значај биоинформатике у интерпретацији података Omics технолunclassified